Tumor cells upregulate normoxic HIF-1α in response to doxorubicin - Cao, Y; Eble, JM; Moon, EJ; Yuan, H; Weitzel, DH; Landon, CD; Yu-Chih Nien, C; Hanna, G; Rich, JN; Provenzale, JM; Dewhirst, MW (American Association for Cancer Research, 2013)
Hypoxia-inducible factor 1 (HIF-1) is a master transcription factor that controls cellular homeostasis. Although its activation benefits normal tissue, HIF-1 activation in tumors is a major risk factor for angiogenesis, therapeutic resistance, and poor prognosis. HIF-1 activity is usually suppressed under normoxic conditions because of rapid oxygen-dependent degradation of HIF-1α. Here, we show that, under normoxic conditions, HIF-1α is upregulated in tumor cells in response to doxorubicin, a chemotherapeutic agent used to treat many cancers. In addition, doxorubicin enhanced VEGF secretion by normoxic tumor cells and stimulated tumor angiogenesis. Doxorubicin-induced accumulation of HIF-1α in normoxic cells was caused by increased expression and activation of STAT1, the activation of which stimulated expression of iNOS and its synthesis of nitric oxide (NO) in tumor cells. Mechanistic investigations established that blocking NO synthesis or STAT1 activation was sufficient to attenuate the HIF-1α accumulation induced by doxorubicin in normoxic cancer cells. To our knowledge, this is the first report that a chemotherapeutic drug can induce HIF-1α accumulation in normoxic cells, an efficacy-limiting activity. Our results argue that HIF-1α-targeting strategies may enhance doxorubicin efficacy. More generally, they suggest a broader perspective on the design of combination chemotherapy approaches with immediate clinical impact.